2022
DOI: 10.1108/cg-01-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee composition and earnings management in a specific institutional environment: the case of Russia

Abstract: Purpose The purpose of this paper is to investigate the specifics of the relationship between audit committee characteristics and earnings management in Russian listed companies. This research is driven by the possibility of placing this relationship within the context of a specific institutional environment for company performance. Design/methodology/approach The authors apply a panel study of 184 Russian listed companies for the period 2014–2018. In addition to the standard fixed effects model, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 124 publications
(207 reference statements)
1
19
0
Order By: Relevance
“…The present study follows two steps to produce a score of four characteristics of the BoD, representing its efficacy. The first step is to measure the four characteristics of director efficacy individually, and these are based on the following metrics: Director independence is the ratio of independent and non-executive directors to the total number of the members of BoD (Bhat et al , 2018; Raimo et al , 2022; Nikulin et al , 2022). Female director representation is the percentage of female directors on corporate boards (Terjesen et al , 2016; Proenca et al , 2020; Saad and Belkacem, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The present study follows two steps to produce a score of four characteristics of the BoD, representing its efficacy. The first step is to measure the four characteristics of director efficacy individually, and these are based on the following metrics: Director independence is the ratio of independent and non-executive directors to the total number of the members of BoD (Bhat et al , 2018; Raimo et al , 2022; Nikulin et al , 2022). Female director representation is the percentage of female directors on corporate boards (Terjesen et al , 2016; Proenca et al , 2020; Saad and Belkacem, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The main responsibilities of an AC include overseeing and monitoring the financial reporting process, identifying and discussing any significant accounting policies, reviewing management's analyses of significant issues in financial reporting and reviewing the effects of regulatory and accounting initiatives (Deloitte 2018). In the context of Russia, a recent study reported that AC representation on the board of directors will lead to a lower EM (Nikulin et al 2022). Likewise, by using meta-analysis, Inaam and Khamoussi (2016) found that an effective AC limits the opportunistic behaviour of management and enhances the supervision of companies.…”
Section: Audit Committee Quality and Earnings Managementmentioning
confidence: 99%
“…Researchers had found an inverse relationship between the independence of EM and AC (Mardessi 2022;Nikulin et al 2022). This line of research suggested that independence of AC may balance the different views between managers and external auditors; and thus, resulting in a higher quality financial report (Kusnadi et al 2015).…”
Section: Audit Committee Quality and Earnings Managementmentioning
confidence: 99%
“…This would help in determining specific corporate governance frameworks according to the institutional context and industry type. Corporate governance and earnings management: Earnings management relates to information manipulation methods that weaken the association between accounting information and a company’s real performance. Fera et al (2022) examine the association between minority directors and earnings management in Italy, while Nikulin et al (2022) examine the relationship between audit committees and earnings management in Russia. There is a need to examine the potential impact of other corporate governance mechanisms on earnings management practices to implement the necessary corporate governance adjustments within companies and improve the quality of accounting information. Corporate governance and integrated financial reporting : Integrated reporting is a vital part of the process of improving a company’s performance by identifying the various factors that influence its sustainable development.…”
Section: Directions For Future Corporate Governance Research Topicsmentioning
confidence: 99%
“…Corporate governance and earnings management: Earnings management relates to information manipulation methods that weaken the association between accounting information and a company's real performance. Fera et al (2022) examine the association between minority directors and earnings management in Italy, while Nikulin et al (2022) examine the relationship between audit committees and earnings management in Russia. There is a need to examine the potential impact of other corporate governance mechanisms on earnings management practices to implement the necessary corporate governance adjustments within companies and improve the quality of accounting information.…”
Section: Directions For Future Corporate Governance Research Topicsmentioning
confidence: 99%